Analysis of surface characteristics and electrochemical corrosion behaviour of WEDMed Ti-6Al-7Nb alloy. (2022) - Singh, Vijender; Katyal, Puneet; Kumar, Kamal
Abstract: In present investigation, surface properties of Ti-6Al-7Nb under rough cut and trim cut modes of WEDMed has been analysed in terms of surface roughness, recast layer, micro hardness and wettability. In continuation to this study, the electrochemical corrosion resistance has been studied for polished and WEDMed samples of Ti-6Al-7Nb alloy. WEDM at the rough cut mode resulted into higher surface roughness, micro-cracks and thickness of a recast layer, whereas trim cut mode produces better surface finish and minimum surface damage. In comparison to polished surface and WEDMed at rough cut mode, trim cut mode results into higher corrosion resistance which is due to the formation of a stable protective rutile-TiO2 layer. WEDMed surface possesses higher wettability as compared to a polished surface.